2018
DOI: 10.1016/j.kjss.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of innovation in creating a competitive advantage

Abstract: This study examined the innovation that leads to a competitive advantage in the frozen food business in the context of small-sized and medium-sized enterprises (SMEs). The research process consisted of three parts: 1) a literature study; 2) an empirical research study using questionnaires as a data collection tool; and 3) an analysis and conclusion of the research results using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM). The findings showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 26 publications
8
140
1
16
Order By: Relevance
“…The considerable change in consumer behavior has prompted the business model innovation of SMTAs, whose sensitivity to the market and ability to respond are largely dependent on their organizational learning ability. The previous studies proposed that organization learning can improve competitive advantages through knowledge sharing and creation [64,72]. Salim and Sulaiman concluded that organizational learning has a positive impact on innovation through their survey on the small and medium-sized enterprises of Malaysia [73].Organizations that have strong learning ability can use internal learning exchange and external learning and communication within an advanced enterprise management model to understand and capture "Internet thinking" as well as use Internet resources to precisely pin down their target market, use innovative methods to meet travelers' needs, and promote value proposition innovation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The considerable change in consumer behavior has prompted the business model innovation of SMTAs, whose sensitivity to the market and ability to respond are largely dependent on their organizational learning ability. The previous studies proposed that organization learning can improve competitive advantages through knowledge sharing and creation [64,72]. Salim and Sulaiman concluded that organizational learning has a positive impact on innovation through their survey on the small and medium-sized enterprises of Malaysia [73].Organizations that have strong learning ability can use internal learning exchange and external learning and communication within an advanced enterprise management model to understand and capture "Internet thinking" as well as use Internet resources to precisely pin down their target market, use innovative methods to meet travelers' needs, and promote value proposition innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Aziz and Samad proposed that innovation is a vital strategic tool to create competitive advantage [63]. Distanont and Khongmalai found that innovation has become an important strategic tool to improve, create and strengthen the competitive advantage of enterprises [64]. While organization can generate knowledge learning, creation and sharing, and grasp external information, thereby creating business performance thorough organizational learning [65].…”
Section: Research Hypotheses and Research Modelmentioning
confidence: 99%
“…Transfer kapitału ludzkiego z międzynarodowych centrów usług a innowacyjność MMŚP Innowacyjność firm, w tym szczególnie firm małych i średnich, zależy od kapitału wiedzy, na którym opierają swoje działania (Łobacz, 2012;Głodek, 2018). Wiedza o różnym charakterze stanowi podstawę i (lub) źródło działań rozwojowych podmiotów gospodarczych (Łobacz, 2015;Łobacz, Głodek, Stawasz, Niedzielski, 2016;Distanont, Khongmalai, 2018). Dlatego efekty zewnętrzne wynikające z przepływu wiedzy stanowią ważną podstawę rozwoju mikro-, małych i średnich firm.…”
Section: Metodologia Badańunclassified
“…Regional competitiveness is closely related to regional economic capabilities, in this case, related to the utilization of regional potential to produce and market products or services needed by the market on an ongoing basis [16]. Some policies that could be implemented are [5], [14], [17], [18]: 1) Improve product quality to meet international standard. 2) Improve clean government and good governance to guarantee business permits services and create a healthy business climate.…”
Section: Developing Local Potency To Strengthen Regional Competitimentioning
confidence: 99%